Introduction of appropriate technology for SMEs of fish cracker in Gresik City - Mochamad Arif Zainul Fuad; Feni Iranawati; Hartati Kartikaningsih (University of Merdeka Malang, 2022)
This community service activity aims to improve the efficiency and competitiveness of Small, Micro, and Medium Enterprises (SMEs) of fish crackers in Pangkahkulon Village, Ujung Pangkah District, Gresik Regency through the introduction of appropriate technology or “Teknologi Tepat Guna” (TTG) in the form of an automatic cracker dough cutting machine. The problem experienced by community service partners is that the thickness of the crackers is not uniform and requires a long cutting time. Through this community service program, partners are provided with automatic cracker cutting machines. In contrast to the many different cutting machines on the market, this machine can directly cut 4-6 pieces at once in one cut, thus producing more slices and saving production time. The results of the practice of using this machine show that this machine can cut very well with a thickness of 1.5-4 mm according to the needs of partners. The thickness of the crackers produced is 2.5±0.3 mm and 2.9±0.3mm which is very in line with the partner's expectations, while if the partner cuts manually the slice thickness is 2.9±0.5 mm and 2.5±0.6mm. The use of this machine also cuts the time for cutting the cracker dough to less than half before, from 2 hours to 1 hour even with a larger amount of cracker dough. The application of appropriate technology can increase the quantity, quality and competitiveness of fish cracker SMEs in Pangkahkulon Village.